Penerapan Model Problem Based Learning (PBL) Terhadap Hasil Belajar Matematika Kelas VIII - Fitriana, Desy; Purwasi, Lucy Asri; Luthfiana, Maria (Universitas Muria Kudus, 2024)
This research aims to determine the completeness of learning outcomes after applying the Problem Based Learning (PBL) learning model in mathematics learning for class VIII students at SMPN 1 Muara Lakitan. The research method used is quasi-experimental with a one-group pre-test and post-test design. The population and sample of all class VIII students at SMPN 1 Muara Lakitan is 20 students. The data collection technique uses an essay test technique with 5 questions. The average value of the learning outcomes of class VIII students at SMPN 1 Muara Lakitan before implementing the Problem Based Learning (PBL) model was 23,09. The average value of student learning outcomes after implementing the Problem Based Learning (PBL) model is 82,65. The data analysis technique uses the t-test formula, based on the results of the hypothesis test, the tcount value is obtained thitung ttabel (7,09 2,093) which means Ho is rejected and Ha is accepted. From the results of the t-test analysis, it can be concluded that the mathematics learning outcomes of class VIII students at SMPN 1 Muara Lakitan after applying the Problem Based leraning model has been significantly completed